1998
DOI: 10.1002/(sici)1097-0207(19980330)41:6<1133::aid-nme329>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method of solving the Navier-Stokes equations for flow control

Abstract: A new method of solving the Navier-Stokes equations e ciently by reducing their number of modes is proposed in the present paper. It is based on the Karhunen-Lo eve decomposition which is a technique of obtaining empirical eigenfunctions from the experimental or numerical data of a system. Employing these empirical eigenfunctions as basis functions of a Galerkin procedure, one can a priori limit the function space considered to the smallest linear subspace that is su cient to describe the observed phenomena, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 6 publications
1
60
0
Order By: Relevance
“…An approach used for highly nonlinear system over a wide range of operating conditions was proposed by Rewienski et al [23,24], where the algorithm presented has been demonstrated to be effective and accurate for highly nonlinear systems, but its performance still depends on a few parameters, which need to be adjusted more or less arbitrarily for a given application example. The reduced-order models generated by the Karhunen-Loeve/Galerkin approach [25,26], on the other hand, are based on the basis functions extracted from an ensemble of the snapshots of the physical fields (e.g., pressure distribution or temperature distribution) under certain actuation conditions, and have been proved to be effective and accurate for macromodeling nonlinear systems too. However, this approach requires expensive coupled-domain FEM/FDM runs to provide enough snapshot data for extracting basis functions.…”
Section: A Automatic Generation Of Macromodelsmentioning
confidence: 99%
“…An approach used for highly nonlinear system over a wide range of operating conditions was proposed by Rewienski et al [23,24], where the algorithm presented has been demonstrated to be effective and accurate for highly nonlinear systems, but its performance still depends on a few parameters, which need to be adjusted more or less arbitrarily for a given application example. The reduced-order models generated by the Karhunen-Loeve/Galerkin approach [25,26], on the other hand, are based on the basis functions extracted from an ensemble of the snapshots of the physical fields (e.g., pressure distribution or temperature distribution) under certain actuation conditions, and have been proved to be effective and accurate for macromodeling nonlinear systems too. However, this approach requires expensive coupled-domain FEM/FDM runs to provide enough snapshot data for extracting basis functions.…”
Section: A Automatic Generation Of Macromodelsmentioning
confidence: 99%
“…Since the empirical eigenfunctions, which constitute the space for the low dimensional dynamic model, are expressed linearly in terms of velocity and temperature fields (Park and Cho 1996;Park and Lee 1998), the velocity and temperature fields must be prepared such that they fully characterize the system dynamics. We assume that the heat flux function qðx; tÞ can be expressed as:…”
Section: Preparation Of Velocity and Temperature Fieldsmentioning
confidence: 99%
“…As explained in Park and Cho (1996) and Park and Lee (1998), the empirical eigenfunctions of the KarhunenLoève decompositions are obtained by solving the following integral equations. where uðxÞ and uðxÞ are the velocity empirical eigenfunction and the temperature empirical eigenfunction, respectively, and K ðvÞ and K ðTÞ are the corresponding twopoint correlation functions defined as:…”
Section: Determination Of Empirical Eigenfuctionsmentioning
confidence: 99%
See 2 more Smart Citations